The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12904-017-0232-x
|View full text |Cite
|
Sign up to set email alerts
|

Translation and cultural adaptation of the Integrated Palliative care Outcome Scale including cognitive interviewing with patients and staff

Abstract: BackgroundTo expand our clinical and scientific knowledge about holistic outcomes within palliative care, there is a need for agreed-upon patient-reported outcome measures. These patient-reported outcome measures then require translation and cultural adaptation, either from country-specific languages to English, or the other way around. The aim of this study was to translate and cross-culturally adapt the Integrated Palliative care Outcome Scale (IPOS) to the Swedish care context.MethodsSwedish versions of IPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 19 publications
2
52
0
Order By: Relevance
“…Comprehension issues consistently reported in the literature concern item Q5, feeling depressed. The association of the term 'depressed' with a medical diagnosis was also noted in a study testing a Swedish version of the IPOS [48]. Similar to our finding, the Swedish research group opted for a colloquial term.…”
Section: Discussionsupporting
confidence: 86%
“…Comprehension issues consistently reported in the literature concern item Q5, feeling depressed. The association of the term 'depressed' with a medical diagnosis was also noted in a study testing a Swedish version of the IPOS [48]. Similar to our finding, the Swedish research group opted for a colloquial term.…”
Section: Discussionsupporting
confidence: 86%
“…IPOS was found to have excellent reliability [12][13][14][15][16] and face and content validity was also confirmed in several studies using cognitive interviews [11,17,18] Convergent validity has been confirmed for the original and German IPOS [13], Japanese version of IPOS [14] and French IPOS [16]. In many other countries the process of validation is ongoing and all language version which are currently available, such as Portuguese, Polish, Greek etc., can be found online (www.pos-pal.org).This study aims to provide a valid version of IPOS in Czech and to report the psychometric properties of IPOS from this first pilot Czech study.…”
Section: Introductionmentioning
confidence: 90%
“…IPOS was found to have excellent reliability (12)(13)(14)(15)(16) and face and content validity was also confirmed in several studies using cognitive interviews (11,17,18) Convergent validity has been confirmed for the original and German IPOS (13), Japanese version of IPOS (14) and French IPOS (16). In many other countries the process of validation is ongoing and all language version which are currently available, such as Portuguese, Polish, Greek etc., can be found online (www.pos-pal.org).This study aims to provide a valid version of IPOS in Czech and to report the psychometric properties of IPOS from this first pilot Czech study.…”
Section: Introductionmentioning
confidence: 82%